MODEL STRUKTURAL PENGARUH KUALITAS PELAYANAN DENGAN WEBQUAL 4.0 TERHADAP KEPUASAN PENGGUNA E-COMMERCE - Asmar AR; Wirawan Setialaksana; Firdaus Firdaus; Alimuddin Sa'ban Miru (Investama : Jurnal Ekonomi dan Bisnis, 2023)
E-commerce in Indonesia is growing very rapidly, with conditions like this indicating an increase in the use of information technology. The quality of e-commerce can affect the number of users who decide to shop online at the e-commerce, the service quality of an e-commerce can affect the number of users who decide to shop at the e-commerce, to determine the effect of service quality on a e-commerce on user satisfaction determined through the webqual 4.0 method. By discussing six aspects of webqual, namely usability, information quality, service interaction, performance, expected quality, and customer satisfaction with e-commerce. With the number of respondents taken as many as 303 respondents using the questionnaire method, then to find out the results of the effect of service quality on user satisfaction using SmartPLS, then an analysis of the data obtained was carried out in the form of analysis with an inductive approach to analyze respondent profiles, presenting data through tables, quantitative analysis includes reliability test, and validity test. Based on the results of the study, it shows that there is a significant influence between variables, namely the quality of usability on user satisfaction, the quality of information on user satisfaction, service interactions on user satisfaction, performance on user satisfaction, and expected quality on user satisfaction.